AUTHORS’ REPLY ON “GEOTECHNICAL HAZARDS IN BANGKOK – PRESENT AND FUTURE” DISCUSSION - Shibuya, S.; Tamrakar, S. B.; Manakul, W. (Lowland Technology International, 2004)
The authors are very much delighted with informative discussion made by our ex-colleagues (and ex-teachers) at AIT. The paper aimed at drawing attention of many readers who may not be familiar with current and, possibly, future geo-hazards in Bangkok area, implying that the paper is a type of incomplete S-O-A report rather than original paper.